Visual and postural control of an arbitrary posture: The handstand - Gautier, G.; Thouvarecq, R.; Chollet, D. (Journal of Sports Sciences, 2007)
The aim of this study was to increase our understanding of postural regulation by analysing an arbitrary posture - the handstand. We assessed the relative influence of peripheral vision and central visual anchoring on the postural balance of gymnasts in the inverted-stand posture. Displacements of the centre of pressure, the angles between the body segments, and the gymnast's height in the handstand were analysed. Postural regulation in the handstand appeared to be organized according to a system similar to that in erect posture, with three articular levels suggesting the existence of a typical organization of human posture. Moreover, both intra-modal (central and peripheral vision) and inter-modal sensory systems (vision and other balance systems) contributed to the postural regulation. The results are interpreted in terms of an ecological approach to posture in which postural regulation can be considered as an emergent phenomenon.